PERFORMANCE EVALUATION OF TWO TYPE OF NUMERICAL DISTANCE RELAYS UNDER FAULT TRANSIENTS (Sciences & Technologie. B, Sciences de l'ingénieur, 2008)
In this paper one considers a numerical distance protection based on the dialogue of two protections using the numerical technology of relay 7SA612 and REL316*4, which constitutes a powerful means interm of speed and of selectivity for the elimination of the lines and bars faults in connecting stations, it canalso ensure a " distant " help under good conditions. This will make it possible to have permanently twoprotections of numerical distance to supervise the decentralized production connected through a HV line.Some simulation results are given to confirm that